Smart Traffic Light Monitoring System for Emergency Vehicle using IoT - Qin, Tan Xiao; Azzali, Fazli (Multidisciplinary Applied Research and Innovation, 2023)
In the modern era, the number of vehicles on the road has increased dramatically. It is because each family will at least own a vehicle. Traffic congestion is becoming one of the most common challenges faced by emergency vehicles such as ambulances, firetrucks and police cars which take more time to reach the destination. The major objective is to improve the traffic conditions by giving priority to emergency vehicles. This project will be developed using NodeMCU ESP8266, infrared sensor and the Firebase database. The result of this project is to improve the performance of the system for detecting emergency vehicles and thus minimize the waiting time due to traffic congestion. As shown in the result, when the sensor detected an emergency vehicle, the traffic light will immediately turn to green light and delay 10 seconds to clear vehicles on that lane. So, the emergency vehicle could pass through the junction without congestion.